P263 De-novo inflammatory bowel disease after bariatric surgery: a novel association. (26th January 2017) - Braga Neto, M.B.; Loftus, E.; Bruining, D.; Bazerbachi, F.; Abu Dayyeh, B.; Raffals, L.; Deepak, P.
Abstract: Background: A reduced alpha diversity in the fecal microbiome of patients with Crohn's disease (CD) has been reported, similar to changes described after bariatric surgery. There have been only 5 case reports of IBD diagnosed in patients with a history of bariatric surgery. Our aim was to identify and characterize patients who were diagnosed with inflammatory bowel disease (IBD), either CD or ulcerative colitis (UC), after having undergone bariatric surgery. Methods: Electronic medical records from January 1996 to January 2016 were reviewed using a bioinformatics search tool at a single institution to identify patients with co-occurrence of an ICD-9/10 code for CD or UC and clinical notes terms associated with bariatric surgery (Roux-en-Y, bariatric surgery, gastroplasty, gastric bypass, gastric sleeve, duodenal switch, gastric banding) were identified and reviewed. Data on demographics, type of bariatric surgical procedure, CD/UC disease phenotype, and medication usage were obtained. Results: A total of 644 patients with co-occurrence of IBD and bariatric surgery were identified with the initial search tool. After record review, 36 patients met inclusion criteria (26 CD and 10 UC). Most patients were female (86.1%). At the time of bariatric surgery, median body mass index (BMI) was 47.2 (Interquartile range (IQR), 42.0–54.2) and age was 38 years (IQR, 30.5–46.7). Median time to IBD diagnosis after bariatric surgery was 6.5 years (IQR, 3.2–8.7); specifically, 6 years for UC and 7 years for CD. Median age at onset of IBD was 44 years (IQR, 38.0–53.7). Family history of IBD and current smoking was present in 5.5% and 30.5% of cases, respectively. Regarding type of bariatric surgery, 75% underwent Roux-en-Y (5 UC and 21 CD), 5.5% gastric banding (1 UC and 1 CD) and 2.7% stapling (1 CD). In the CD group, the most common disease location was ileal (50%) followed by ileocolonic (34.6%). Most CD patients had inflammatory disease behavior (73.1%) followed by penetrating (15.3%) and stricturing disease (11.6%). In patients with UC, 50% had extensive colitis, followed by left-sided colitis (30%) and proctitis (20%). Tumor necrosis factor-alpha inhibitors were used in 42.3% of CD and 10% of UC patients. Overall, 47.2% of IBD patients required hospitalization (50% in UC and 46.1% in CD) and 25% required surgical intervention for treatment of their disease (20% in UC and 26.9% in CD. Conclusions: We have described a case series of patients developing de-novo IBD after bariatric surgery. This potential association requires confirmation in larger patient cohorts.